Clutch sizes of the Spectacled Eider on the Yukon-Kuskokwim Delta, Alaska - Dau, Christian P (Wildfowl, 1976)
Nesting patterns of the Spectacled Eider Somateria fischeri on the Yukon-Kuskokwim Delta appear to be dictated by the timing and duration of the spring break-up period. Late springs which retarded nest site availability reduced both nesting density and clutch size. Available information suggests that female Spectacled Eiders return to previously used nesting areas. Renesting of this species has not been recorded on the Yukon Kuskokwim Delta but has been observed on their Siberian nesting grounds. Observations suggest that only adult females nest on the Yukon Kuskokwim Delta however nesting of sub-adult females appears to occur in Siberian nesting areas.